Effect of intense physical exercise on hepcidin levels and selected parameters of iron metabolism in two different trial of training - Skarpanska-Stejnborn, A.; Basta, P.; Trzeciak, J.; Kafkas, E.; Latour, E.; Cieslicka, M. (Science & Sports, 2019)
Research question: The aim of the study was to analyse changes in selected pro-inflammatory cytokines and parameters of iron metabolism, observed after an intense ergometric test conducted during two different phases of a yearly training cycle. Research methods: The study included a group of elite rowers (n=15). During each of the analysed training phases, the athletes were subjected to a 2000-m ergometric exercise test. Results and findings: Irrespective of the training phase, similar levels of IL-6, hepcidin and sTfR were found in blood samples collected immediately after the ergometric tests. In contrast, post-exercise levels of Fe, TNF-a and CK were significantly higher in material collected after the test conducted during the competitive phase of a yearly training cycle. This study of elite rowers showed that physical exercise may stimulate changes in the pro-inflammatory profile of blood serum, via the influence on TNF-a levels. This effect is modulated by a number of training-related factors that acted prior to the ergometric test, such as exercise frequency and intensity. Implications: Therefore, post-training adaptation to physical exercise is not always sufficient, which may result in the impairment of the immune response and thus negatively affect iron metabolism.